2010
DOI: 10.1128/jcm.00728-10
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Rabies Virus Reverse Transcription-PCR and Virus Isolation Using Samples from a Patient Infected with Rabies Virus

Abstract: Definite and rapid diagnosis of rabies is required for individual case management as well as for public health. For the first time, a direct comparison of virus isolation with quantitative real-time reverse transcription (RT)-PCR on human rabies samples was conducted. RT-PCR was found to be more sensitive than virus isolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…A number of real-time RT-PCRs have been designed for specifically detecting individual strains or lineages of RABV 2 and also to detect lyssaviruses across the genus 3,4,5,6,7,8,9 . All assays will have a limit of detection dependent on how conserved the primer (and if necessary, the probe) sequences are across the genus.…”
Section: Introductionmentioning
confidence: 99%
“…A number of real-time RT-PCRs have been designed for specifically detecting individual strains or lineages of RABV 2 and also to detect lyssaviruses across the genus 3,4,5,6,7,8,9 . All assays will have a limit of detection dependent on how conserved the primer (and if necessary, the probe) sequences are across the genus.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, repeated sampling of skin biopsies is not practical for improvement of sensitivity of the FAT (10,14,15). To overcome the limits of FAT, several conventional and hemi-nested reverse transcription polymerase chain reaction assays (RT-PCR) targeting the N or L gene, have been developed (16,17,18,19,20,21,22) and widely applied for the intra-vitam diagnosis of human rabies routine diagnosis. Indeed, the N gene is the most conserved region among the RABV genome which is the reason for its frequent use as target for rabies virus diagnostic assays (23).…”
Section: Introductionmentioning
confidence: 99%
“…Superiority of the real time RT‐PCR over the conventional virus isolation methods has been reported for many other viruses such as influenza virus [Pregliasco et al, ; Steininger et al, ], respiratory syncytial virus [Reis et al, ], Rabies virus [Panning et al, ], Dengue virus [Azhar et al, ], and the human metapneumovirus [Matsuzaki et al, ]. Extensive work by several authors on diagnosis of the human metapneumovirus also showed that virus isolation was only successful in 33–50% of cases in which samples were diagnosed to be positive by RT‐PCR [Williams et al, ; Ebihara et al, ; Kahn, ; Collins and Crowe, ].…”
Section: Discussionmentioning
confidence: 99%